2020
DOI: 10.14306/renhyd.24.4.984
|View full text |Cite
|
Sign up to set email alerts
|

Programas de intervención a través de Internet para la reducción de peso en adultos con sobrepeso y obesidad: una revisión sistemática

Abstract: Introducción: el auge de la tecnología ha posibilitado el desarrollo de programas vía Internet para abordar el problema de la obesidad, como apoyo complementario a programas presenciales. El presente estudio evalúa la evidencia sobre programas vía Internet realizados en personas adultas con sobrepeso y  obesidad, analizando los recursos y componentes principales de las intervenciones. Material y métodos: Se realizó una revisión sistemática en las bases de datos Web of Science y Scopus. Se seleccionaron estudio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…We rated two reviews as being of moderate methodological quality [ 6 , 37 ], 13 as low [ 19 , 20 , 23 , 25 – 27 , 29 , 31 , 32 , 33 ••, 34 , 38 •, 43 ], and 11 as critically low [ 21 , 22 , 24 , 28 , 30 , 35 , 36 , 39 42 ]. A detailed evaluation of each AMSTAR 2 criteria can be found in the Online Resource .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We rated two reviews as being of moderate methodological quality [ 6 , 37 ], 13 as low [ 19 , 20 , 23 , 25 – 27 , 29 , 31 , 32 , 33 ••, 34 , 38 •, 43 ], and 11 as critically low [ 21 , 22 , 24 , 28 , 30 , 35 , 36 , 39 42 ]. A detailed evaluation of each AMSTAR 2 criteria can be found in the Online Resource .…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen reviews reported weight loss outcomes by comparing intervention effects to any control conditions, including standard care, waitlists, paper-based communication, or minimal interventions such as an educational website or a single face-to-face educational session [ 19 , 20 , 22 – 28 , 30 , 31 , 34 – 37 , 40 , 42 ].…”
Section: Resultsmentioning
confidence: 99%